A revision of the genus Andesipolis (Hymenoptera: Braconidae: Mesostoinae) and redefinition of the subfamily Mesostoinae - Shimbori, Eduardo Mitio; Souza-Gessner, Carolina Da Silva Souza; Penteado-Dias, Angelica Maria; Shaw, Scott Richard (Zootaxa, 2017)
Mesostoinae is a poorly understood subfamily, with a classic Gondwanan distribution. Historically, its members have been classified in as many as nine different subfamilies and/or tribes. Formally comprising seven genera (Andesipolis, Aspilodemon, Hydrangeocola, Opiopterus, Mesostoa, Praonopterus and Proavga), there are at least six more genera (Apoavga, Austrohormius, Canberria, Doryctomorpha, Hormiitis and Neptihormius) to be included based on morphological and geographical data. Here, we discuss the placement of the Neotropical genus Andesipolis Whitfield & Choi within Mesostoinae, and provide a revised definition of the subfamily. We revise the genus Andesipolis, and provide descriptions of 22 new species from Argentina, Brazil, Chile, Colombia and Ecuador. A key to known species is also presented. The distribution of Andesipolis is exclusive to high altitude or high latitude regions in South America, especially in mountain ranges along the Pacific and Atlantic coasts.